Analysis of reasons for organ donor shortage and the main directions of its overcoming - S. F. Bagnenko; Yu. S. Polushin; Ya. G. Moisyuk; A. O. Reznik; I. V. Loginov; I. V. Pogrebnichenko; O. N. Reznik (Трансплантология (Москва), 2018)
Deficit of donor organs is main critical factor limiting of organ transplantation. In article highlighted the organ donation practice in SaintPetersburg with accent on unsuccessful attempts of the increasing of number deceased organ donors. Given by analyses of neurosurgical and neurological rates of mortality last three years, the authors tried to ground the urgency of the putting in clinical practice the optimization of the transplant algorithms, organ donor’s audit, and the implementation of new approach to define organ donor’s process stages. In article are presented the results worked out of the metrics coefficients for estimating donation potential of emergency hospitals. There was done the study of involvement and education in organ donation practice, legislative issues among critical care professionals, neurologists and critical care nurses. In articles is presented the first attempt of estimate of economical aspects of donation process in donor’s hospitals. There was done the recommendation for national organ donation network creating.